Learning from France: using public deliberation to tackle infrastructure planning issues. Issue 4 (1st October 2016) - Marshall, Tim
ABSTRACT: This paper examines the practice in France since the 1990s in working towards decisions on major infrastructure. Whilst in some European countries the drive since that time has been to press faster decision-making and deregulation, in France the response to difficulties in progressing large infrastructure schemes was to move to more deliberative approaches, both at the project level and in relation to environmental issues as a whole. The paper considers these approaches alongside the growing literature on deliberative democracy, particularly that on deliberative systems. It is suggested that there is much scope to learn from the accumulated experience in these fields, which could help to provide a more considered, open and pluralist approach to infrastructure decisions, genuinely taking account of all alternatives, as against the tendency to move to a more demand driven and limited democracy approach which has been promoted in England and Wales in the UK and to a certain extent at EU level as well.